Nutrition for Hypercholesterolemic Children - Martín-Martínez, Benjamín; López-Liñán, María José (Journal of Child Science, 2018)
In the diet of hypercholesterolemic children, 10 to 18% of the total calorie intake should be protein, 50 to 60% carbohydrates, and 30% lipids, of which less than 10% should be saturated fatty acids, between 7 and 10% should be polyunsaturated fatty acids, and 10 to 20% should be monounsaturated fatty acids. Cholesterol intake should not exceed 300 mg/dL, and an adequate fiber intake of 8 to 28 g/day, according to the child's age, should be ensured. If a child is obese or overweight, the aim of the initial treatment should be to normalize weight through improved lifestyle habits, dietary recommendations, and increased physical activity. The healthy diet for cardiovascular disease prevention is similar to that advised for a healthy pediatric population: (1) reduced total fat intake, such as through eating less red meat and sausages and choosing skimmed milk, butter, skimmed-milk cheese, lean meat, skinless chicken, and rabbit, cooked using simple cooking processes; (2) increased intake of monounsaturated and polyunsaturated oils, such as fish oil and olive oil; (3) reduced cholesterol intake, such as through the reduced consumption of eggs, viscera, and industrial bakery products; and (4) higher intake of fish and complex carbohydrates, such as pasta, pulses, and whole-grain bread. In addition, fruits and vegetables should be recommended for their fiber, vitamins, minerals, and trace elements. The recommended culinary preparation is to grill, steam, or bake food and to avoid frying, especially with butter or animal fat, and to give preference to oils based on monounsaturated fats, such as olive and sunflower oil.
Keywords: hypercholesterolemia; nutrition; dietary patterns; children